2006
DOI: 10.1248/cpb.54.114
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Cinnamaldehyde, Eugenol and Paeonol in Traditional Chinese Medicinal Preparations by Capillary GC-FID

Abstract: Key words GC; cinnamaldehyde; eugenol; paeonol; traditional Chinese medicinal preparation through a 0.45 mm membrane filter for GC analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Based on these considerations, the simultaneous analysis of cinnamaldehyde and benzaldehyde are very important. Trans-cinnamaldehyde has been determined by spectrofluoromety (Tsai and Chen 1984), highperformance liquid chromatography (HPLC; Katayama, Mukai, and Taniguchi 1990;Lee et al 1995;Okamura et al 1999), micellar electrokinetic chromatography (Huang, Kuo, and Hsieh 1997), and gas chromatography (Friedman, Kozukue, and Harden 2000;Yu, Lai, and Tan 2006;Blakemore and Thompson 1983). Also, the benzaldehyde was analyzed by several methods such as differential pulse polarography (Kazemifard et al 2002), HPLC (Shemesh, Karschimkus, and Rowley 2005), gas chromatography (GC; Kazemifard et al 2003;Hignite, Shen, and Azarnoff 1978), and derivative ultraviolet (UV) spectrometry (Hewala 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these considerations, the simultaneous analysis of cinnamaldehyde and benzaldehyde are very important. Trans-cinnamaldehyde has been determined by spectrofluoromety (Tsai and Chen 1984), highperformance liquid chromatography (HPLC; Katayama, Mukai, and Taniguchi 1990;Lee et al 1995;Okamura et al 1999), micellar electrokinetic chromatography (Huang, Kuo, and Hsieh 1997), and gas chromatography (Friedman, Kozukue, and Harden 2000;Yu, Lai, and Tan 2006;Blakemore and Thompson 1983). Also, the benzaldehyde was analyzed by several methods such as differential pulse polarography (Kazemifard et al 2002), HPLC (Shemesh, Karschimkus, and Rowley 2005), gas chromatography (GC; Kazemifard et al 2003;Hignite, Shen, and Azarnoff 1978), and derivative ultraviolet (UV) spectrometry (Hewala 1993).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some research groups reported that flavoring additives in food could also be detected by GC and GC-MS, such as menthol in food 6 , eugenol in fish and shrimp muscle tissue 710 as well as vanillin in fruit juice and milk powder 1,11 . Additionally, GC and GC-MS have been extensively applied for other assay fields, such as determination of eugenol in traditional Chinese medicine 12 , menthol and methyl salicylate in human plasma 13 , vanillin and ethyl vanillin in vanilla extract products 14 , methyl salicylate in ulmus pumila leaves 15 , and menthol in traditional Chinese medicinal herbs 16 . Nevertherless, previously reported methods mainly focused on the detection of one flavor agent in food, and the challenging of the parallel detection of several flavor agents was rarely addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Chromatographic techniques like liquid chromatography – mass spectrometry, gas chromatography – mass spectrometry, high – performance liquid chromatography, and ultra – performance liquid chromatography – electro spray mass spectrometry have been used earlier to determine paeonol in plant samples and in biochemical analysis. Capillary electrophoresis has also been used for the simultaneous determination of paeonol with cinnamaldehyde and eugenol . Quantum dots based fluorescence quenching method has been used for the determination of paeonol in ointment ,.…”
Section: Introductionmentioning
confidence: 99%